PROBLEM SOLVING WITH THE HELP OF EQUATIONS AND INEQUATIONS - BRĂDULEAC, Iraida (Acta et Commentationes, Sciences of Education, 2022)
Problem solving is an in-depth activity, with the character of superior analysis and synthesis. The activity of solving school mathematics problems is an optimal framework for cultivating creativity, especially for the development of logical thinking. Solving problems tests the intellectual abilities of students to the highest degree, requires all their mental availability, especially intelligence.